(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Digital transformation is fundamentally changing the approach to natural resource management in both the private and public sectors. In the context of increasing regulatory requirements and growing pressure on companies to integrate sustainable business models, digital technologies offer new opportunities for monitoring, optimization and transparency. At the same time, the public sector has an important role to play in stimulating sustainable practices through regulations, public policies and smart resource management. The mechanism of responsible governance in the context of digital and sustainable transformation is the object of the study and the aim is to analyze and evaluate how digitalization and sustainable management strategies can support effective natural resource management in the private and public sectors, focusing on the role of CSR. The objectives are: to investigate the main digital technologies and their application in natural resource management; to analyze the ESM strategies in enterprises and their impact on sustainable management; to assess the role of the public sector in supporting digital sustainable practices; to identify synergy between the public and private sectors for more effective natural resource management. The research thesis is that the successful combination of digital technologies and sustainable management practices leads to more effective and transparent natural resource management in both the corporate and public sectors, with CSR acting as a bridge between the two sectors. The results are expressed in: 1) digital technologies significantly improve natural resource monitoring, analysis and management. 2) ESG reporting and CSR are key enablers for integrating sustainable strategies into business, with management increasingly using automated platforms to assess environmental impacts. 3) the public sector plays an important role in promoting sustainable transformation through regulations, subsidies and smart infrastructure projects. 4) there are significant opportunities for synergy between business and the public sector through partnerships, data sharing and innovation in natural resource management.